Mevinolin: a highly potent competitive inhibitor of hydroxymethylglutaryl-coenzyme A reductase and a cholesterol-lowering agent. - Alberts, A W (1980)
Mevinolin, a fungal metabolite, was isolated from cultures of Aspergillus terreus. The structure and absolute configuration of mevinolini and its open acid form, mevinolinic acid, were determined by a combination of physical techniques. Mevinolin was shown to be 1,2,6,7,8,8a-hexahydro-beta, delta-dihydroxy-2,6-dimethyl-8-(2-methyl-1-oxobutoxy)-1-naphthalene-hepatanoic acid delta-lactone. Mevinolin in the hydroxy-acid form, mevinolinic acid, is a potent competitive inhibitor of 3-hydroxy-3-methylglutaryl-coenzyme A reductase [mevalonate: NADP+ oxidoreductase (CoA-acylating), EC 1.1.1.34]; its Ki of 0.6 nM can be compared to 1.4 nM for the hydroxy acid form of the previously described related inhibitor, ML-236B (compactin, 6-demethylmevinolin). In the rat, orally administered sodium mevinolinate was an active inhibitor of cholesterol synthesis in an acute assay (50% inhibitory dose = 46 microgram/kg). Furthermore, it was shown that mevinolin was an orally active cholesterol-lowering agent in the dog. Treatment of dogs for 3 weeks with mevinolin at 8 mg/kg per day resulted in a 29.3 +/- 2.5% lowering of plasma cholesterol.